2023
DOI: 10.1038/s41392-022-01259-6
|View full text |Cite
|
Sign up to set email alerts
|

Targeting integrin pathways: mechanisms and advances in therapy

Abstract: Integrins are considered the main cell-adhesion transmembrane receptors that play multifaceted roles as extracellular matrix (ECM)-cytoskeletal linkers and transducers in biochemical and mechanical signals between cells and their environment in a wide range of states in health and diseases. Integrin functions are dependable on a delicate balance between active and inactive status via multiple mechanisms, including protein-protein interactions, conformational changes, and trafficking. Due to their exposure on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
111
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 324 publications
(191 citation statements)
references
References 598 publications
(861 reference statements)
1
111
0
2
Order By: Relevance
“…In the current study, the most common concurrent mutation was TP53 . As a well‐known tumor suppressor gene, TP53 mutation has been widely observed in various cancer types, causing the dysfunction of transcription factor p53 and a series of biological function disorders 42 . Previous studies have revealed that EGFRm patients harboring coexisting TP53 mutation had significantly shorter survival time and quicker development of drug resistance than those with TP53w , 43–45 which was verified in our study by showing a 7.6‐months shorter PFS in the TP53m subgroup than the TP53w subgroup.…”
Section: Discussionsupporting
confidence: 83%
“…In the current study, the most common concurrent mutation was TP53 . As a well‐known tumor suppressor gene, TP53 mutation has been widely observed in various cancer types, causing the dysfunction of transcription factor p53 and a series of biological function disorders 42 . Previous studies have revealed that EGFRm patients harboring coexisting TP53 mutation had significantly shorter survival time and quicker development of drug resistance than those with TP53w , 43–45 which was verified in our study by showing a 7.6‐months shorter PFS in the TP53m subgroup than the TP53w subgroup.…”
Section: Discussionsupporting
confidence: 83%
“…Due to the targeting of RGD peptides, peptide-coated Pt clusters can bind with αvβ3 expression in cells ( Guo et al, 2014 ; Yuan et al, 2014 ; Ludwig et al, 2021 ; Pretze et al, 2021 ; Pang et al, 2023 ; Yin et al, 2023 ). Confocal laser scanning microscopy (CLSM) was used to verify the specificity target of Pt in SiHa cells.…”
Section: Resultsmentioning
confidence: 99%
“…P53 is a tumor suppressor gene, which is one of the most common mutation genes in various human tumors. It participates in various activities of cells, such as cell cycle arrest, apoptosis, autophagy, DNA repair, etc 40 . Studies comparing wild‐type and p53 deficient mice show that p53 is necessary for radiation‐induced cell apoptosis, 41 and p53 mutation increases the radioresistance of cancer cells, and partial recovery of p53 function causes radiosensitization 42 .…”
Section: Discussionmentioning
confidence: 99%